The Role of Microtubules in Pancreatic Cancer: Therapeutic Progress - Albahde, Mugahed Abdullah Hasan; Abdrakhimov, Bulat; Li, Guo-Qi; Zhou, Xiaohu; Zhou, Dongkai; Xu, Hao; Qian, Huixiao; Wang, Weilin (Frontiers in Oncology, 2021)
Pancreatic cancer has an extremely low prognosis, which is attributable to its high aggressiveness, invasiveness, late diagnosis, and lack of effective therapies. Among all the drugs joining the fight against this type of cancer, microtubule-targeting agents are considered to be the most promising. They inhibit cancer cells although through different mechanisms such as blocking cell division, apoptosis induction, etc. Hereby, we review the functions of microtubule cytoskeletal proteins in tumor cells and comprehensively examine the effects of microtubule-targeting agents on pancreatic carcinoma.